2018
DOI: 10.2337/db18-129-lb
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Blood Pressure Control, Metabolic Parameters, and Target Organs Protection with Perindopril + Indapamide Fixed Combination in Hypertensive Patients with Obesity and Prediabetes

Abstract: The study objective was to evaluate the ability of the fixed combination (FC) of perindopril + indapamide (P+I) to reduce insulin resistance and low intensive noninfectious inflammation as well as to improve arterial elasticity in patients with hypertension, obesity and prediabetes on previous successful antihypertensive therapy with losartan + hydrochlorothiazide (L+HTZ) 100/12.5 mg. A 12-week open-label study included 50 patients (age 54.8 ± 6.6 years, body mass index (BMI) 32.5 ± 3.2 kg/m2). All patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The benefits of a Per/Ind SPC in patients with uncontrolled hypertension and obesity and prediabetes have also been observed in a 12-week open-label study [48], which showed that the Per/Ind SPC achieved further decreases in BP over a previous losartan ? hydrochlorothiazide diuretic combination.…”
Section: Cholesterol Total Cholesterolmentioning
confidence: 72%
“…The benefits of a Per/Ind SPC in patients with uncontrolled hypertension and obesity and prediabetes have also been observed in a 12-week open-label study [48], which showed that the Per/Ind SPC achieved further decreases in BP over a previous losartan ? hydrochlorothiazide diuretic combination.…”
Section: Cholesterol Total Cholesterolmentioning
confidence: 72%
“…В. Недогода и соавт. [36], изучали возможности фиксированной комбинации индапамид/периндоприл (И/П) 2,5 мг/10 мг в ангиопротекции у пациентов с АГ, достигших и не достигших целевого АД<140/90 ммрт. ст.…”
unclassified